Um estudo do hidrogênio neutro e rádio contínuo em galáxias seyfert com mopra e atca - Adornes, Rosane Bohrer (2006)
In this work 21-cm observations of a sample of 27 southern nearby galaxies (z < 0:018) are presented with a detected Hi line with the Mopra/ATNF radiotelescope. The total neutral hydrogen gas content has been derived and it has been found that sample galaxies classified as Seyfert have high neutral gas content with an average value of Hi mass to total blue luminosity of MHI=LB ∼ 0:38Mʘ=Lʘ which tends to increase with decreasing optical and infrared luminosities. I also found a correlation between the neutral gas content of Seyfert-type II galaxies and IRAS luminosities similar to those found for normal spirals and high-mass starburst galaxies. The Australia Telescope Compact Array has been used to obtain radio continuum images of the galaxies NGC1566, NGC1672, NGC3109, NGC4945, NGC5068, NGC6221, NGC6684, NGC6744, IC5201, NGC7314 and NGC 7424 in 1380 MHz. The main source structure have been detected within a ∼ 12 kpc field from the optical cores and are partially resolved in the images. Nuclear magnetic fields obtained from minimum energy considerations are between 20 and 80 µG. These fields are confined to the galactic nuclei and are at least 15 times greater than those found in normal spiral disks. Star-formation models suggest that the circunuclear radio emission can be explained by massive star formation with rates equivalent to those found in spiral disks with SFR ∼ 0:03 Mʘ yr−1 up to values as high as 6.0 Mʘ yr−1. A correlation between the nuclear radio power and infrared luminosities is seen in the galaxies in our sample. The results are interpreted within a scenario that star formation in Seyfert galaxies is similar to those found in nearby starbursts which is dependent to the initial mass content from the disk progenitors in the sequence blue compact galaxies - Hii galaxies - Seyferts, where the total infrared luminosity and the total hydrogen mass are well related LFIR=Lʘ ∝ (MHI=Mʘ)1:5±0:4. The analysis of our results it has also resulted in a Person correlation coefficient of 0.4 between the dynamic mass and the Hi content.